2019
DOI: 10.1111/echo.14312
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of two‐dimensional speckle tracking echocardiography to identify ischemic etiology of left ventricular systolic dysfunction

Abstract: Background The differentiation between dilated cardiomyopathy (DCM) and systolic dysfunction caused by coronary artery disease (CAD) based on clinical and echocardiographic presentation can be difficult in some cases. Aim Our study aimed to define differences in myocardial function between patients with ischemic and nonischemic etiology of reduced left ventricular ejection fraction using 2D speckle tracking echocardiography (STE). Material and methods We retrospectively analyzed 90 patients (mean age 65 ± 11 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It can predict severe coronary artery disease (CAD) in women with normal LV function [ 17 ]. It can be used to identify the ischemic etiology of LV systolic dysfunction [ 18 ]. The study by Atici et al showed that GLS (global longitudinal strain) evaluated through 2D-STE is a potential method for predicting CAD in patients with non-ST-segment elevation myocardial infarction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can predict severe coronary artery disease (CAD) in women with normal LV function [ 17 ]. It can be used to identify the ischemic etiology of LV systolic dysfunction [ 18 ]. The study by Atici et al showed that GLS (global longitudinal strain) evaluated through 2D-STE is a potential method for predicting CAD in patients with non-ST-segment elevation myocardial infarction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining parameters as mentioned above did not differ significantly in the study groups. The area under the ROC curve was 0.64 (95% CI 0.5315–0.7381 and P = 0.018), with rather limited sensitivity and specificity for diagnosis of obstructive CAD, that is, 73% and 53%, respectively . Clearly, the concept is novel, and the results are provocative/exciting and perhaps hypothesis‐generating.…”
mentioning
confidence: 99%
“…The area under the ROC curve was 0.64 (95% CI 0.5315-0.7381 and P = 0.018), with rather limited sensitivity and specificity for diagnosis of obstructive CAD, that is, 73% and 53%, respectively. 11 Clearly, the concept is novel, and the results are provocative/exciting and perhaps hypothesis-generating. The idea to discern the etiology of heart failure (ischemic vs nonischemic) needs to be further studied/…”
mentioning
confidence: 99%